Public Policy Strategy for Cost-effective Road-traffic Safety - Suleimenov, Daniyar (Nazarbayev University Graduate School of Public Policy, 2017)
In the modern day world, increasing number and power of vehicles on the road has caused road casualties number to increase rapidly. The World Health Organisation (WHO) provides that 1.24 million lives were lost worldwide to road accidents in 2010 and this number is expected to rise to 1.9 in 2020. In modern-day Kazakhstan increased car ownership has followed economic growth pattern throughout the XXI century. This has in turn caused increased number of deaths from road accidents per capita - the statistic peaked at 28.19 per 100,000 of population in 2008 (from 18.47 in 2003). In this regards Kazakhstan measured poorly both against close neighbours and other countries, both developing and developed. The cost of road casualties expressed as a factor of value of human life lost or impaired, loss of productive capacity, loss of human consumption, medical and other related costs has the potential to undermine the country’s capacity for sustainable development.
Keywords: public policy; road-traffic Safety; road-traffic